The Snow Queen - Andersen, Hans Christian (Usborne Publishing Ltd; UK, 2004)
Designed for young children who are just beginning to read alone and are looking for lively stories to tackle. Colorful pictures combine with narrative text written to encourage reading skills for developing and emerging readers. AGe 5+